PERAN DAKWAH HABIB HASAN AL MUNAWAR PADA KULINER DAN ADAT KEBIASAAN KOTA PALEMBANG-SUMATERA SELATAN - Rhiza Eka Purwanto; Melati Pratama (Fakultas Dakwah dan Komunikasi, 2017)
Al-Munawar is one of the names of an Arab village in Palembang city, which is on the outskrirts of the river Musi precisely in the 13 Ulu area of Palembang. Al Munawar Arab village set by Department of Tourism and Culture of South Sumatera Province as one of the historical and religious tourism destination. History tells, the formation of the village begins from the commerce of Sriwijaya kingdom until period between the collapse of Sriwijaya kingdom and the emergence of Palembang Sultanate that is 1500-1700 M. In the beginning, the immigrants who are brokers are not allowed to live in the land of Sriwijaya so they living on the outskirts and the moving to house above the Musi riverbanks, living in groups by maintaining the tradition of the origin culture. One such resident is Habib Hasan Al Munawar. Along with the existance of his descendants in the city of Palembang, causing Palembang has a culinary, how to serve and how to culinary different cuisines. The purpose of this study is :1. Identify culture and culinary of the descendants of Al Munawar in Palembang, 2. Identify the culinary linkages of the Al Munawar tribes in the village of Al Munawar Palembang, 3. Knowing of the role of Habib Hasan in the customs of Palembang people to eat culinary.